(untitled) (Jurnal Bahasa, 2014)
This article aims to identify and discuss the politeness strategies in the perbilangan adat (customary sayings) in the adat perpatih. The data for this research are the customary sayings used in four negotiation events of the adat perpatih: istiadat kerjan (appointment ceremony), istiadat memulih pusako (reinstatement ceremony), istiadat berkodim (change of clan ceremony) and the engagement ceremony. The data is analysed qualitatively using politeness principles (Leech, 1983). The findings show that the politeness strategies in the customary sayings, particularly those used in negotiations to send a certain message, reflect in the implied meanings of the utterances of the speaker. The linguistic features of the customary sayings, which include figurative language, euphemisms, and local dialect or expressions, result in politeness in communication, and cooperation among the participants involved in the negotiations. Keywords: linguistic politeness, istiadat kerjan, istiadat memulih pusako, istiadat berkodim, engagement ceremony